Hafnia Ferroelectric Thin Films: Compensation Charge Control and Modeling for Reproducing Negative Capacitance Effect of Hafnia Ferroelectric Thin Films (Adv. Mater. Interfaces 23/2020). Issue 23 (3rd December 2020) - Ahn, Dante; Jung, Moonyoung; Lee, Yoseop; Song, Sungmun; Ham, Woori; Suh, Dongseok; Ahn, Seung‐Eon
Abstract : The negative capacitance effect is reproduced by controlling the imbalance between the polarization conversion amount and the compensation charge amount. The physical phenomena occurring in the ferroelectric thin film are analyzed considering the impedance of each component, and a ferroelectric capacitor equivalent circuit model based on the RC parallel circuit is proposed. More details can be found in article number 2001356 by Seung‐Eon Ahn and co‐workers.